PENGALIHAN OBJEK GADAI MOTOR DI DESA SAI KECAMATAN SOROMANDI DALAM PERSPEKTIF HUKUM EKONOMI SYARIAH - Amrin; Moh. Asyiq Amrulloh (Universitas Islam Negeri Mataram, 2021)
The practice of pawning does not always correspond to what happens in the real world, as is the case in the Sai Village community, Soromandi District. In the case of the transfer of the object of the pawn of a motorbike which is done unilaterally, it means that the party holding the pawn pawns the goods that are still in the status of collateral to another party (third party) which in this case is to his own relatives or neighbors. Then the pawn object (motorcycle) changes hands by being handed over to a third party because the pawnbroker needs money to increase capital, farm, and for educational purposes for his children, as a result the goods that are the object of the pawn collateral are transferred to another party without the knowledge of the pawnbroker (owner of the pawned goods).